Cyber threats and scams in FinTech organizations: a brief overview of financial fraud cases, future challenges, and recommended solutions in Bangladesh - Hossain, Md. Jafrin; Rifat, Rejuan Haque; Mugdho, Mahadi Hasan; Jahan, Mohona (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.